Antibacterial Activity of Transparent Soap Added Avocado Oil and Telang Flower Extract (Clitoria ternatea) - Muhammad Zulham Effendi Sinaga; Sri Wulandari (Journal of Chemical Natural Resources, 2024)
Telang flowers contain secondary metabolites, one of which is antibacterial because it has potential as an alternative to antibiotics. The purpose of the research was to increase the function of transparent soap moisturise the skin and inhibit the growth of bacteria on the skin's surface. The butterfly pea flower was extracted by maceration using 96% ethanol, and then the extract was added to the making of transparent soap according to the treatment. The treatments in this study were the addition of S0 (0 mL) butterfly pea flower extract as a control; S1 (0,10 mL); S2 (0,15 mL); S3 (0,20 mL); S4 (0,25 mL) into 100 mL of transparent soap formulation. The best formulation resulting from this study was the S4 treatment (6 g cocoa butter, 7 g stearic acid, 14 g palm oil, 5 g avocado oil, 48% NaOH 7 g, 13 g glycerin, 15 g ethanol, cocamide- DEA 5 g, 17 g sugar, 0.2 g NaCl, 10.45 g aquadest and 0.3 g perfume and 0.05 g dye. The results of the antibacterial activity produced from the butterfly pea flower extract and avocado oil resulted in an inhibitory effect on P. acne bacteria ranging from 8,1-20,1 mm, which had moderate to strong inhibition, and E. coli bacteria ranged from 21,1-28,8 mm which had very strong inhibition.